Genetic evaluation for biometrical traits in fennel (Foeniculum vulgare Mill.) - Y C Yadav, S K Rawat, S Kumar (Journal of Spices and Aromatic Crops, 2013)
The genetic variability, heritability, genetic advance, phenotypic coefficient of variation (PCV) and genotypic coefficient of variation (GCV) of 13 diverse genotypes of fennel were studied. Considerable amount of variation were recorded for all the characters. The phenotypic coefficient of variation (PCV) was higher than genotypic coefficient of variation (GCV) in all the characters. The maximum genotypic coefficient of variation (GCV) was recorded for yield plant-1 (40.27) followed by seed yield (32.40 q ha-1), weight of seed umbel-1 (27.12), number of umbellets umbel-1 (17.47) and number of seeds umbel-1 (16.88). High heritability coupled with high genetic advance were recorded for number of seeds umbel-1, yield plant-1, plant height, number of umbel plant-1 and number of branches plant-1.